Antecedents of Regional Financial Independence: A Moderating Effect of Capital Expenditure at Local Government Level in Indonesia - Qoriiba, Fathan; Aswar, Khoirul; Ermawati (Journal of Economics and Behavioral Studies, 2021)
This study aims to examine regional tax, general allocation fund, special allocation fund, and capital expenditure as a mediating on regional financial independence. Regency/City in West Java Province was used as a sample in this study. The purposive sampling method was used in this study to select a sample of 27 districts/cities in West Java Province from 2016 to 2019. Hypotheses in this study were tested using Structural Equation Model using Smart PLS 3.0 software. This study results in Regional Tax, General Allocation Fund, and Special Allocation Fund have a significant effect on regional financial independence, while capital expenditure is not able to mediate the effect of regional tax, general allocation fund, and special allocation fund on regional financial independence. For Local Governments, it is expected to optimize local taxes through the improvement of adequate public services. Then, given that the composition of general allocation funds and special allocation funds is quite dominant, the funds should be optimized for the development sectors so that their use can be efficient which will encourage economic growth and indirectly increase regional financial independence.